2020
DOI: 10.1177/2325967120929349
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Use of Regional Anesthesia and Postoperative Patterns of Opioid Prescription Filling in Shoulder Arthroscopy: A Procedure-Specific Analysis in Patients With or Without Recent Opioid Exposure

Abstract: Background: There are few large database studies on national trends in regional anesthesia for various arthroscopic shoulder procedures and the effect of nerve blocks on the postoperative rate of opioid prescription filling. Hypothesis: The use of regional nerve block will decrease the rate of opioid prescription filling after various shoulder arthroscopic procedures. Also, the postoperative pattern of opioid prescription filling will be affected by the preoperative opioid prescription-filling history. Study D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 44 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…Following this, 120 full-text articles were reviewed, and 14 met the inclusion criteria. 12,21,27–38 Seven of these 14 studies were randomized controlled trials (RCTs), 12,21,27,29–31,37 and 7 were nonrandomized studies, 28,32–36,38 including 3 prospective observational studies (POSTs) 28,32,38 and 4 retrospective cohort studies (RCSs). 33–36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, 120 full-text articles were reviewed, and 14 met the inclusion criteria. 12,21,27–38 Seven of these 14 studies were randomized controlled trials (RCTs), 12,21,27,29–31,37 and 7 were nonrandomized studies, 28,32–36,38 including 3 prospective observational studies (POSTs) 28,32,38 and 4 retrospective cohort studies (RCSs). 33–36…”
Section: Resultsmentioning
confidence: 99%
“…34,35 This effect applied to both patients who received either single-shot regional anesthesia or continuous regional anesthesia in the form of a plexus catheter (Table 2). 34,35…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies in opioid consumption in the shoulder and elbow literature address opioid usage after shoulder procedures, primarily shoulder arthroplasty and rotator cuff repair. [16][17][18][19][20][21][22] One previous study examined risk factors for chronic opioid use after elbow arthroscopy. 23 In this study, Rojas et al using data from a national database found that preoperative opioid filling, fibromyalgia, and psychiatric illness were associated with an increased risk of prolonged postoperative opioid use after elbow arthroscopy, whereas patients <40 years of age and chronic obstructive pulmonary disease were associated with a decreased risk.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies in opioid consumption in the shoulder and elbow literature address opioid usage after shoulder procedures, primarily shoulder arthroplasty and rotator cuff repair. 16 , 17 , 18 , 19 , 20 , 21 , 22 One previous study examined risk factors for chronic opioid use after elbow arthroscopy. 23 In this study, Rojas et al.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of literature has suggested that the use of regional anesthesia (RA) techniques has increased over time 1–3. Potential benefits of RA include decreased risk of postoperative infection,4 increased same-day postoperative discharge rates,5 decreased postoperative complications,6 and decreased postoperative opioid requirements 7–9.…”
Section: Introductionmentioning
confidence: 99%